ANALISIS KREDIT MACET DAN IMPLEMENTASI RESTRUKTURISASI KREDIT : (Studi Kasus Koperasi Kredit Syuradikara) - Ta , Valeria Rofina; Djou, Laurentius D Gadi; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2020)
Syuradikara Credit Cooperative (KKS) is one of the cooperatives that is experiencing bad credit. Bad credit that occurs is due to the inability of customers to pay loan installments, as a result, it can reduce the income of the cooperative. One of the steps taken by the KKS to resolve this bad credit is by restructuring. The purpose of this study was to determine: (1). factors that lead to bad credit on KKS and (2), steps in the implementation of restructuring in settling bad debts on KKS. The data analysis used is descriptive analysis using a qualitative approach. The results of this study indicate that: (1). The factors that cause bad credit on KKS, namely from internal factors, include the KKS not being observant in deciding the size of loan services to members, lack of education for members and prospective borrowers, and less competent credit staff. Meanwhile, external factors include members who are not used properly, lazy attitude, wastefulness, lack of diligence in doing business and the backbone of the family who dies or is looking for a place to work overseas. (2). The steps for implementing restructuring in settling bad debts include giving a warning or warning letter, conducting routine billing, working with the police to pick up members to sign a statement of ability to pay arrears, and making renewals, namely by rescheduling.